Trading motives in asset markets - Zijian Wang (The University of Western Ontario, Department of Economics, 2019)
I study how trading motives in asset markets affect equilibrium outcomes and welfare. I focus on two types of trading motives - informational and allocational. I show that while a fully separating equilibrium is the unique equilibrium when trading motives are known, multiple equilibria exist when trading motives are unknown. Moreover, forcing traders to reveal their trading motives may harm welfare. I also use this model to study how an asset market may exit a fire sale equilibrium and how government programs may eliminate private information and improve agents' welfare.
Keywords: G12; D82; D83; G18; 330; asset markets; private information; competitive search; government intervention